Tensions within the left in a local industrial milieu: Puente Alto 1936-1953 - Navarro Martínez, Juan José (Revista de Historia Social y de las Mentalidades, 2025)
This paper analyzed the relationship between socialists and communists during the Popular Front and radical governments in Puente Alto. In this territory, the municipality was administered by socialist militants until 1953, while these also deployed their presence in the Paper Union of the Paper and Cardboard Manufacturing Company, where they coincided with communist militants. Frictions and conflicts were identified in both spaces, providing new background on their relationship at the national level. Methodologically, the analysis was focused on the conflictive knots reflected in the dissemination organs of both groups. The main conflicts developed in three dimensions: communal administration, union hegemony and repercussions of national politics. Although the enmities were fed by the international and national context, local disputes, slander and the search for representation of the popular sectors of the commune also played a key role.